The young lady from Paris : a novel - Aiken, Joan, 1924-
The Paris Girl is about a young French woman, Andrée Griotteray White, living in her hometown of Paris at the time of the German occupation of Paris during WWII. It was written by her own daughter, Francelle Bradford White, French through her mother and British through her father. White used her mother’s journals and diaries written from this time period, supplemented by discussions with her maternal grandparents, her mother, and her uncle, Alain Griotteray, who played a major role in the resistance movement.